High cerebrospinal fluid lactate concentration at 48 h of hospital admission predicts poor outcomes in patients with tuberculous meningitis: A multicenter retrospective cohort study - Liu, Chenchao; Huai, Ruixue; Xiang, Yijia; Han, Xu; Chen, Zixiang; Liu, Yuhan; Liu, Xingjun; Liu, Huiquan; Zhang, Hong; Wang, Sihan; Hao, Lingyu; Bo, Yin; et al. (Frontiers in Neurology, 2022)
Objective: This study aimed to analyze the cerebrospinal fluid (CSF) parameters affecting the outcomes of patients with tuberculous meningitis (TBM). Methods: This is a multi-center, retrospective, cohort study involving 81 patients who were diagnosed with TBM and treated in Haihe Clinical College of Tianjin Medical University, Tianjin Medical University General Hospital, and General Hospital of Air Force PLA from January 2016 to December 2019. Baseline data, Glasgow Coma Scale (GCS) score, and clinical presentations of all patients were collected at admission. CSF samples were collected at 48 hours, 1, 2, and 3 weeks after admission. CSF lactate, adenosine deaminase, chloride, protein, glucose levels and intracranial pressure were measured. After a follow-up of 16.14±3.03 months, all patients were assessed using the modified Rankin Scale (mRS) and divided into good (mRS scores of 0-2 points) and poor outcome groups (mRS scores of 3-6 points). The differences in patients’ baseline data, GCS score, clinical presentations, and levels of CSF parameters detected at 48 hours, 1, 2, and 3 weeks after admission between two groups were compared. Statistically significant variables were added to the binary logistic regression model to identify the factors impacting the outcomes of patients with TBM. Receiver operating characteristic (ROC) curve was used to assess the predictive ability of the model Results: The CSF lactate level exhibited a decreasing trend within 3 weeks of admission in the two groups. For the within-group comparison, statistically significant differences in the lactate level was found in both groups between four different time points. A binary logistic regression model revealed that CSF lactate level at 48 hours after admission, age, and GSC score on admission were independently associated with the outcomes of patients with TBM. ROC curve analysis showed that the area under the ROC curve (AUC) was 0.786 for the CSF lactate level (48H), 0.814 for GCS score, and 0.764 for age. Conclusion: High CSF lactate level at 48 hours after admission is one of the important factors for poor outcomes in patients with TBM.